Feeding management of crossbred dairy cows in the central Ethiopian highlands - Mamo, S.; Zerbini, E.; Yami, A. (British Society of Animal Science, 1998)
In Ethiopia, Boran and Arsi indigenous cows have been crossbred with Friesian and, or, Jersey sires in an attempt to increase milk production, especially in the Highlands (Kiwawa et al., 1983; Beyene, 1984). However, significant increase in milk production from crossbred cows have been constrained by insufficient supplies of quality forage and supplement feeds and inadequate management practices (Varvikko, 1991). Performance of F1 Friesian x Boran crossbred cows in smallholder farms in the Central Ethiopian Highlands varied greatly among farms (Ludstrom, 1991). Annual shortages of energy and protein could only explain part of the observed variation. There is therefore, a need to identify additional factors affecting the productive performance of these improved genotypes in smallholder farms. Feed allocation priorities to different cattle types in each farm could have contributed to performance differences of crossbred cows and eexplain some of the variation observed. The objective of the study was to identify differences in land and livestock holding and the feeding practices in farms with higher and lower producing crossbred cows of the same genotype.